The Role of Transformational Leadership in the Implementation of Child-Friendly School Policy - Sulistyowati, Titik; Ginting, Rosalina Br; Muhtarom, Muhtarom (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
The Implementation of the Child-Friendly School (Sekolah Ramah Anak/SRA) policy is a strategic effort to ensure the fulfillment of children’s rights and to create a safe, inclusive, and child-centered educational environment. However, the effectiveness of this policy largely depends on school leadership, particularly the Principal’s transformational leadership. This study aims to analyze the role of principals’ transformational leadership in implementing the Child-Friendly School policy at SMP Negeri 1 Tegowanu. The research employed a qualitative descriptive approach. Data were obtained from primary and secondary sources involving the Principal, teachers, students, parents, and school committee members. Data collection techniques included in-depth interviews, participatory observations, and documentation studies conducted at SMP Negeri 1 Tegowanu. Data were analyzed using interactive analysis techniques: data collection, data reduction, data display, and conclusion drawing. Data validity was ensured through technique triangulation, source triangulation, and time triangulation. The findings indicate that principals’ transformational leadership plays a crucial role in supporting the Implementation of the Child-Friendly School policy through four interrelated dimensions. Inspirational motivation encourages teachers to continuously develop their competencies, significant experiences, and Collaborative Innovation through collaborative problem-solving and the adoption of child-friendly learning strategies. Individualized consideration is reflected in the Principal’s attention to individual differences, recognition of achievements, and personalized support for school members. Idealized influence is demonstrated through exemplary behavior, integrity, and strong commitment to child protection principles. The novelty of this study lies in identifying collective decision-making as a key leadership practice that strengthens policy implementation and ensures the fulfillment of children’s rights in a non-discriminatory manner.